ARE MUSLIM DOMESTIC TRAVELERS CONCERNS ABOUT SUSTAINABLE TOURISM BY EATING LOCAL FOODS? A CASE STUDY IN INDONESIA - Makarim, Akmal Andira; Muslichah, Istyakara (MANAJEMEN DEWANTARA, 2024)
This study aims to examine the impact of local food on economic, socio-cultural, environmental, and tourism sustainability in four Indonesian cities: Solo, Semarang, Bandung, and Yogyakarta. The sampling method used is quota sampling with the criteria of Muslim domestic travelers who have visited the four cities. This study obtained 202 respondents and the data were processed using the PLS-SEM method. The variables used in this study are local food, economic sustainable tourism, socio-cultural sustainable tourism, and environmental sustainable tourism. The results show a positive and significant impact of local food consumption on economic sustainability, leading to improved economic conditions in the cities studied. In addition, the promotion and awareness of local cuisine also contribute to socio-cultural sustainability. The study highlights the positive impact of local food on environmental sustainability. The study shows that practices such as minimizing food miles can help reduce environmental degradation. In addition, the study shows that local food has a positive and significant impact on sustainable tourism.